FEATURES OF CLINICAL COURSE AND MORPHOLOGICAL CHANGES OF CHRONIC HEPATITIS C IN INFANTS - M. M. Kotovich; F. K. Manerov; N. A. Karnauhova (Детские инфекции (Москва))
The authors have observed 37 young children with chronic viral hepatitis C of different route: perinatal — 24 children (group 1) and not perinatal — 13 patients (group 2). The clinical picture and morphological pattern of the infection depending on the route of the infection have been presented. In case of perinatal infection, some children showed physical developmental disabilities and malabsorption syndrome. The biochemical activity was predominantly minimal in group 1 and low in group 2. Histological changes in liver tissue were revealed in all the young children with chronic hepatitis C. However, the inflammatory activity in the liver tissue is more prominent in children of the group 2, and the degree of fibrosis is more prominent in children from group 1. Only in case of perinatal infection the direct correlation between elevated levels of ALT and AST and the presence of fibrosis in the liver tissue has been revealed revealed.